Assessment of body-powered 3D printed partial finger prostheses: a case study - Keaton J. Young; James E. Pierce; Jorge M. Zuniga (3D Printing in Medicine, 2019)
Abstract Background Traditional prosthetic fabrication relies heavily on plaster casting and 3D models for the accurate production of prosthetics to allow patients to begin rehabilitation and participate in daily activities. Recent technological advancements allow for the use of 2D photographs to fabricate individualized prosthetics based on patient anthropometrics. Additive manufacturing (i.e. 3D printing) enhances the capability of prosthesis manufacturing by significantly increasing production speed and decreasing production cost. Existing literature has extensively described the validity of using computer-aided design and 3D printing for fabrication of upper limb prostheses. The present investigation provides a detailed description of the development of a patient specific body-powered 3D printed partial finger prosthesis and compares its qualitative and functional characteristics to a commercially available finger prosthesis. Case presentation A 72-year old white male with a partial finger amputation at the proximal interphalangeal joint of the left hand performed a simple gross motor task with two partial finger prostheses and completed two self-reported surveys (QUEST & OPUS). Remote fitting of the 3D printed partial finger began after receipt of 2D photographs of the patient’s affected and non-affected limbs. Prosthetic fitting when using 3D printable materials permitted the use of thermoforming around the patient’s residual limb, allowing for a comfortable but tight-fitting socket. Results of the investigation show improved performance in the Box and Block Test when using both prostheses (22 blocks per minute) as compared to when not using a prosthesis (18 blocks per minute). Both body-powered prostheses demonstrated slightly lower task-efficiency when compared to the non-affected limb (30 blocks per minute) for the gross motor task. Results of the QUEST and OPUS describe specific aspects of both prostheses that are highly relevant to quality of life and functional performance when using partial finger prostheses. Conclusion The use of 3D printing exhibits great potential for the fabrication of functional partial finger prostheses that improve function in amputees. In addition, 3D printing provides an alternative means for patients located in underdeveloped or low-income areas to procure a functional finger prosthesis.